2018
DOI: 10.1002/mp.12955
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric and geometric characteristics of a small animal image‐guided irradiator using 3D dosimetry/optical CT scanner

Abstract: This study demonstrated that 3D PRESAGE dosimeters can be used for verification of precise targeting for the SARRP. This 3D dosimetry system can be utilized to obtain information on both geometric and dosimetric properties, as well as acquire beam data parameters for the purpose of commissioning image-guided small animal irradiator systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The excellent agreement between the measurements acquired from PRESAGE and the manufacturer’s Monte‐Carlo based values indicates that PRESAGE is a suitable dosimeter for 3D dosimetry and for clinical research. It is important to mention that small discrepancies were observed between EBT3 film and PRESAGE measurement for low energy applications and small field dosimetry . The main advantages of using PRESAGE over other types of dosimeters include its linear response to the absorbed dose over a wide dose range, its tissue‐equivalency over a wide energy range, and its capability to provide 3D dose distribution with high resolution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The excellent agreement between the measurements acquired from PRESAGE and the manufacturer’s Monte‐Carlo based values indicates that PRESAGE is a suitable dosimeter for 3D dosimetry and for clinical research. It is important to mention that small discrepancies were observed between EBT3 film and PRESAGE measurement for low energy applications and small field dosimetry . The main advantages of using PRESAGE over other types of dosimeters include its linear response to the absorbed dose over a wide dose range, its tissue‐equivalency over a wide energy range, and its capability to provide 3D dose distribution with high resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The dosimetric characteristic of PRESAGE polyurethane dosimeters (Heuris Inc., Skillman, New Jersey, NJ, USA), formulated with a halogenated hydrocarbon free radical initiator and leuco dye has been thoroughly investigated and is well-characterized. [1][2][3][4][5][6][7] A 2009 Radiologic Physics Center phantom study investigating the 3D dosimetric applications of PRESAGE showed good agreement (98% pass rate with gamma criteria of 4%, 3 mm) of PRESAGE measurement with EBT radiochromic film (Ashland Inc., Wilmington, DE, USA) measurement for a Head and Neck Intensity Modulated Radiation Therapy (IMRT) plan. 4 Additionally, PRESAGE was used to measure Gamma Knife Perfexion output factors in 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although efforts have been made to ensure high geometric accuracy with SA‐IGRT systems, the main challenge with these approaches is that they cover only limited aspects. For example, several investigators have quantified the accuracy of mechanical or rotational isocenters in novel small animal IGRT, X‐RAD, and SARRP systems. The isocentricity of the stage rotation was determined for the SARRP system .…”
Section: Introductionmentioning
confidence: 99%
“…For example, several investigators have quantified the accuracy of mechanical or rotational isocenters in novel small animal IGRT, X‐RAD, and SARRP systems. The isocentricity of the stage rotation was determined for the SARRP system . The congruence of imaging and delivery isocenters was characterized on the Stanford modified micro‐CT system, X‐RAD, and SARRP systems.…”
Section: Introductionmentioning
confidence: 99%